Decreasing arsenic accumulation in rice by overexpressing OsNIP1;1 and OsNIP3;3 through disrupting arsenite radial transport in roots - Sun, Sheng‐Kai; Chen, Yi; Che, Jing; Konishi, Noriyuki; Tang, Zhong; Miller, Anthony J.; Ma, Jian Feng; Zhao, Fang‐Jie (The New phytologist, 2018)
Rice is a major dietary source of the toxic metalloid arsenic. Reducing arsenic accumulation in rice grain is important for food safety. We generated transgenic rice overexpressing two aquaporin genes, OsNIP1;1 and OsNIP3;3, under the control of a maize ubiquitin promoter or the rice OsLsi1 promoter, and tested the effect on arsenite uptake and translocation. OsNIP1;1 and OsNIP3;3 were highly permeable to arsenite in Xenopus oocyte assays. Both transporters were localized at the plasma membrane. Knockout of either gene had little effect on arsenite uptake or translocation. Overexpression of OsNIP1;1 or OsNIP3;3 in rice did not affect arsenite uptake but decreased root-to-shoot translocation of arsenite and shoot arsenic concentration markedly. The overexpressed OsNIP1;1 and OsNIP3;3 proteins were localized in all root cells without polarity. Expression of OsNIP1;1 driven by the OsLsi1 promoter produced similar effects. When grown in two arsenic-contaminated paddy soils, overexpressing lines contained significantly lower arsenic concentration in rice grain than the wild-type without compromising plant growth or the accumulation of essential nutrients. Overexpression of OsNIP1;1 or OsNIP3;3 provides a route for arsenite to leak out of the stele, thus restricting arsenite loading into the xylem. This strategy is effective in reducing arsenic accumulation in rice grain.